The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.30880/jtet.2019.11.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Employment Skills Among Malaysian Vocational Students: An Analysis of Gender Differences

Abstract: Employability and the creation of a knowledge-based economy have become fundamental concerns in many countries, including Malaysia. Realizing the need to achieve a high-income economy, the Malaysian Government through its Eleventh Malaysia Plan (2016-2020) is transforming Technical and Vocational Education Training (TVET) by enabling industry-led approach is crucial to produce skills human capital that meet the industry demand and support the migration of all economic sectors towards knowledge intensive activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
0
0
Order By: Relevance
“…As such, graduating students should have a proactive grasp of technology from existing institutions of higher learning (Adeyinka-Ojo et al, 2020), while higher education institutes must emphasize developing knowledge and attributes that prepare students for the careers they wish to pursue (Chen & Gursoy, 2008;Schreck et al, 2020). Employability skills involve the ability to contribute to work efficiency in an organization combined with good oral and written communication skills and critical thinking, which form the foundation of both academic and workplace success (Munro, 2007;Mahazir et al, 2019).…”
Section: Knowledgementioning
confidence: 99%
See 2 more Smart Citations
“…As such, graduating students should have a proactive grasp of technology from existing institutions of higher learning (Adeyinka-Ojo et al, 2020), while higher education institutes must emphasize developing knowledge and attributes that prepare students for the careers they wish to pursue (Chen & Gursoy, 2008;Schreck et al, 2020). Employability skills involve the ability to contribute to work efficiency in an organization combined with good oral and written communication skills and critical thinking, which form the foundation of both academic and workplace success (Munro, 2007;Mahazir et al, 2019).…”
Section: Knowledgementioning
confidence: 99%
“…The concept of employability skills can be broadly defined as the academic, personal, and teamwork skills that employers expect of their employees, and these skills should be developed through education (Ismail et al, 2019). Meanwhile, previous research found that the implementation of team-based learning in the education system is crucially important to develop the student's skills and competencies that are useful for enterprises, organizations, occupations, and teams to perform various tasks (Lu, 2021).…”
Section: Skillmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in China, Zeng et al (2022) find that male vocational students are more driven and exhibit elevated energy when it comes to adapting to work. But, as stated by Ismail et al (2019), in some countries, the percentage of females enrolled in TVET is lower than males due to factors such as the government itself, school society and parents. The finding from the study by Abdullah et al (2020), shows that there is a statistical difference between male and female students in vocational colleges on social intelligence, cross-cultural skills, and leadership skills.…”
Section: Gender Differences In Employability Among Vocational College...mentioning
confidence: 99%